Religious and Cultural Foundations of School-Parent Partnerships in an Outstanding Islamic Elementary School - Syaiful Arifin; Wahidmurni; Marno; Siti Marpuah; Nur Rohman (Mimbar Agama Budaya, 2026)
Partnerships between educational institutions and parents are crucial in building a supportive environment for the academic and non-academic successes of students. This study aims to describe the organization and development of school-parent collaborations by SD Muhammadiyah 4 Surabaya (Mudipat), one of the prominent Islamic elementary schools, to improve student achievement. The research employed a qualitative methodology and a case study framework to gather data through in-depth interviews, document analysis, and observations. Data analysis was performed using the following methods: data condensation, data display, and conclusion drawing. The findings present that strategic school-parent partnerships at Mudipat are based on well-articulated principles like internal solidarity, prioritization of systems over individuals, commitment and consistency, contribution, satisfaction, social responsibility, responsiveness to the needs of the school, and utilization of networks. The principles are operationalized through practices such as the Muhammadiyah Parents Association (IKWAM), which involves parents at the personal and institutional levels in the school's decision-making process, ensuring transparency in management, and providing the best services to students and parents. The study concludes that well-managed strategic school-parent partnerships significantly enhance support for students' academic and non-academic success.